A Portrait of Religious Moderation Strategy of the Guru Penggerak in Interfaith School Learning in Cirebon City - Habibi, Debi Fajrin (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2024)
This study aims to analyze the strategies, creations, and innovations of driving teachers in integrating the value of religious moderation in religious subjects at school. This research uses a qualitative method by applying a descriptive-analytical approach. The results and discussion show that strengthening religious moderation in education is important as an effort to prevent students from extreme and radical views that lead to terrorism. World civilization in the current era must be equipped with a qualified understanding of religious practices in facing a multicultural society. Religious science and natural science work together in exploring the roots of faith or the founding of civilization. The basis for this integration is the unity of sources, goals, means and groups of knowledge. Religious science offers the purpose of life. Natural sciences offer the means necessary to realize these goals. The positive trend of civilization will continue as long as harmony is created between religious and scientific understanding. This research recommends to the position holders, school leaders in the world of education, students, communities, and other stakeholders not to be easily carried away by radicalism and terrorism.